Growth mechanism of InGaN nano-umbrellas. (11th October 2016) - Zhang, Xin; Haas, Benedikt; Rouvière, Jean-Luc; Robin, Eric; Daudin, Bruno
Abstract: It is demonstrated that growing InGaN nanowires in metal-rich conditions on top of GaN nanowires results in a widening of the InGaN section. It is shown that the widening is eased by stacking faults (SFs) formation, revealing facets favorable to In incorporation. It is furthermore put in evidence that partial dislocations terminating SFs efficiently contribute to elastic strain relaxation. Indium accumulation on top of the InGaN section is found to result in an axial growth rate decrease, which has been assigned to increased N–N recombination and subsequent effective nitrogen flux decrease, eventually leading to the formation of InGaN nano-umbrellas/nanoplatelets.